1994
DOI: 10.1007/bf02355652
|View full text |Cite
|
Sign up to set email alerts
|

Structural organization of the sensory systems of the snail

Abstract: The author's data on the structural organization of the nervous system of the body wall, the gravitational organs (the statocysts, the eyes, and the chemosensory organs), and the head tentacles of the snails Helix vulgaris and Helix pomatia are correlated in this paper. The localization in the CNS and some structural characteristics of the central divisions of the sensory systems are shown. Information is presented on the structure of the procerebrum, an associative center participating in the processing of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 37 publications
1
25
1
Order By: Relevance
“…Our results indicate that the observed spreading of the EP to the area of oscillations may be a result of the overlapping of the neuropile projection (the part of PC where the EP has been recorded) and the projection of the cell body layer where the oscillations are most expressed (Delaney et al 1994) to the two-dimensional plane of the photodiode array. This interpretation is in accord with the olfactory nerve backfill data (Zaitseva 1991;Chase and Tolloczko 1993). These authors demonstrated that the olfactory nerve fibers do not reach the cell body layer: They terminate in the procerebral neuropile, at the border of the cell body layer and the neuropile.…”
Section: Nikitin and Balabansupporting
confidence: 75%
See 3 more Smart Citations
“…Our results indicate that the observed spreading of the EP to the area of oscillations may be a result of the overlapping of the neuropile projection (the part of PC where the EP has been recorded) and the projection of the cell body layer where the oscillations are most expressed (Delaney et al 1994) to the two-dimensional plane of the photodiode array. This interpretation is in accord with the olfactory nerve backfill data (Zaitseva 1991;Chase and Tolloczko 1993). These authors demonstrated that the olfactory nerve fibers do not reach the cell body layer: They terminate in the procerebral neuropile, at the border of the cell body layer and the neuropile.…”
Section: Nikitin and Balabansupporting
confidence: 75%
“…The nerve contains axons of sensory neurons as well as the axons of tentacular ganglion projection interneurons (Chase and Tolloczko 1993). The nerve backfills demonstrate that the majority of olfactory axons branch and terminate in the PC (Zaitseva 1991;Chase and Tolloczko 1993). The synaptic connections of those neurons occur both in the neuropile and in the cell body layer, as shown by intracellular staining of individual procerebral neurons (Ratté and Chase 1997).…”
Section: Nikitin and Balabanmentioning
confidence: 99%
See 2 more Smart Citations
“…[4], Achatina fulica [5]), the cellular organization of PCs from different molluscs share a number of common features. Track tracing experiments have revealed the members of the neuronal afferents and the types and morphology of PC interneurons [5,6,7,8,9,10]. In addition to morphological findings, electrophysiological recording has also demonstrated that the population of PC cells within the layer where the perikarya of PC interneurons are located (the cell mass layer) consists of large number (75%) of non-bursting (NB) neurons with small size (5-8 μm), and a smaller number (25%) of bursting (B) neurons of larger size (10-15 μm) [11,12].…”
Section: Introductionmentioning
confidence: 99%